International norms for adult handgrip strength: A systematic review of data on 2.4 million adults aged 20 to 100+ years from 69 countries and regions - Grant R. Tomkinson; Justin J. Lang; Lukáš Rubín; Ryan McGrath; Bethany Gower; Terry Boyle; Marilyn G. Klug; Alexandra J. Mayhew; Henry T. Blake; Francisco B. Ortega; Cristina Cadenas-Sanchez; Costan G. Magnussen; et al. (Journal of Sport and Health Science)
Background: Muscular strength is a powerful marker of current health status and robust predictor of age-related disease and disability. Handgrip strength (HGS) using isometric dynamometry is a convenient, feasible, and widely used method of assessing muscular strength among people of all ages. While adult HGS norms have been published for many countries, no study has yet synthesized available data to produce international norms. The objective of this study was to generate international sex- and age-specific norms for absolute and body size-normalized HGS across the adult lifespan. Methods: Systematic searches were conducted in 6 databases/web search engines (MEDLINE, SPORTDiscus, Embase, Web of Science, CINAHL, and Google Scholar) up to December 1, 2023. We included full-text peer-reviewed observational studies that reported normative HGS data for adults aged ≥20 years by sex and age. Pseudo data were generated using Monte Carlo simulation following harmonization for methodological variation. Population-weighted Generalized Additive Models for Location, Scale, and Shape were used to develop sex- and age-specific norms for absolute HGS (kg) and HGS normalized by height (Ht, m) squared (i.e., HGS/Ht2 in kg/m2). Norms were tabulated as percentile values (5th to 95th) and visualized as smoothed percentile curves. Results: We included data from 100 unique observational studies representing 2,405,863 adults (51.9% female) aged 20 to 100+ years from 69 countries and regions tested from the year 2000 onward. On average, absolute and normalized HGS values negligibly improved throughout early adulthood, peaked from age 30–39 years (at 49.7 kg (males) and 29.7 kg (females) for absolute HGS or 16.3 kg/m2 (males) and 11.3 kg/m2 (females) for HGS/Ht2), and declined afterwards. The age-related decline in HGS accelerated from middle to late adulthood and was slightly larger for males than for females during middle adulthood. Conclusion: This study provides the world's largest and most geographically comprehensive international norms for adult HGS by sex and age. These norms have utility for global peer-comparisons, health screening, and surveillance.